The use of the geographic scale in health: the scales of visceral leishmaniasis - Silvestre Matsumoto, Patricia Sayuri [UNESP]; Zampieri D'Andrea, Lourdes Aparecida (Abrasco-assoc Brasileira Pos-graduacao & Saude Coletiva, 2019)
The geographical scale has been broadly discussed in an attempt to formulate a concept that succeeds in explaining different space-related realities. In the various sectors of health planning, geographic categories and concepts have been adopted without understanding the problems inherent to the geographical scale, which directly affects public policies implemented and, consequently, people's lives. The scope of this paper was to discuss the concept of scale based on the different scale levels and the difficulty of their implementation by menus of the activities of the organs that operate in public health surveillance that deal with visceral leishmaniasis. A systematic review of the literature was conducted to show how the debate about geographical scale and health is still incipient. Geographical concepts were used, integrating municipal, state and national policies from the perspective of the geographic scale. Thus, the contention is that cooperation between health agencies and society is possible by the transposition of scales, creating an environment of solidarity and a more effective health system. The discussion does not end here, but it will make it viable to reflect on the theoretical and methodological options in research and in public health.
Keywords: Scales; Geographic scale; Health systems agencies; Visceral leishmaniasis; Public health surveillance